Polwan dan Kekerasan dalam Rumah Tangga (KDRT): Analisis Kasus Pembakaran Suami Di Mojokerto Dari Perspektif Gender dan Hukum - Novita Irene Wong; Joko Sriwidodo; Edi Saputra Hasibuan (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Cases of gender-based violence in the family (KDRT) continue to be an important issue because of its major impact. Gender stereotypes that consider men as perpetrators and women as victims often ignore the fact that women can also be perpetrators. This study uses a normative approach with an analysis of laws and regulations, cases, and literature studies to understand the influence of gender roles in KDRT and the application of the law to perpetrators who are members of the police. The results of the study indicate the need for inclusive legal reform and an understanding of gender equality to ensure equal legal protection for all victims. In cases of KDRT involving female police officers, the application of the PKDRT Law is more relevant because it regulates physical violence that causes death. Handling this case requires a transparent, fair, and objective legal process, regardless of the status of the perpetrator